Reduced graphene oxide-titania nanocomposite-modified photoanode for efficient dye-sensitized solar cells - Lim, Su Pei; Pandikumar, Alagarsamy; Huang, Nay Ming; Lim, Hong Ngee (John Wiley & Sons, 2015)
We report the successful application of reduced graphene oxide–titania (rGO–TiO2) nanocomposite as an efficient photoanode for dye‐sensitized solar cell (DSSC). The DSSC assembled with the rGO–TiO2‐modified photoanode demonstrated an enhanced solar to electrical energy conversion efficiency of 4.74% compared with the photoanode of DSSC composed with unmodified TiO2 (2.19%) under full sunlight illumination (100 mW/cm2, AM 1.5G) as a result of the better charge collection efficiency of rGO, which reduced the back electron transfer process. Influence of the rGO content on the overall efficiency was also investigated, and the optimal rGO content for TiO2 was 0.5 mg. Further, the modification of rGO–TiO2 on the compact layer TiO2 surface led to an increase in efficiency to 5.83%. The superior charge collection and enhanced solar energy conversion efficiency of the rGO–TiO2 nanocomposite makes it to be used as a promising alternative to conventional photoanode‐based DSSCs.